(untitled) (Journal of the College of Basic Education, 2026)
This research aims to develop a proposed strategy based on polytechnical theory. To achieve this goal, the researcher followed the procedures of the descriptive method in developing the proposed strategy for the curriculum and instruction course in colleges of education. This involved several stages, beginning with planning, which included (justifications for developing the proposed strategy, its foundations, and identifying the sources of development). The analysis and design-development stage included (identifying the basic premises, determining the cognitive, psychological, social, and technological foundations, defining the general objectives, selection criteria, and the steps for its implementation within the classroom, which were: preparation, the productive situation, collaborative production, practical application, and feedback). The group review, linking, and comprehensive evaluation,” and also in light of the steps, the researcher formulated the characteristics of the proposed strategy and presented a set of pillars. The result of the research was the construction of the strategy in a good way, the formulation of its theoretical and procedural definition, the determination of its goals and philosophy, the determination of the role of the teacher and the learner in it, the educational means, and the methods of evaluation. The researcher recommended a number of recommendations and suggested a number of proposals.